RESERCH OF THE IMPACT OF OPERATING CONDITIONS ON THE TECHNICAL CONDITION OF HYDRAULIC CYLINDERS OF A FORKLIFT TRUCK - STRELBITSKIY, VICTOR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Forklifts are widely used for lifting and transporting various loads in warehouses of sea and river ports [1-7]. In particular, due to its characteristic properties: versatility, economy, high mobility and maneuverability (moving cargo in different directions in a limited space). The performance of Port lines depends on their reliable and continuous operation. The introduction of hydraulic drives can significantly improve the performance of forklifts. The wide use of which is due to a number of advantages: relatively small dimensions and weight, smooth running, the ability of the working fluid to compensate for shock loads, etc. However, severe operating conditions and cyclic loading modes negatively affect the efficiency of loaders due to the reduced durability of the hydraulic drive. In addition, the durability of the hydraulic drive of the machine is determined by the service life of its components. As practical experience shows, the most frequent failures are the result of gross violations of the operating conditions and maintenance requirements specified by the manufacturer [1,5-7]. To ensure the reliability and durability of hydraulic drives, a comprehensive and complex solution is needed, which provides for qualitative and quantitative analysis of the causes of malfunctions, analysis of the impact of operating factors on performance during Operation. The aim of the work is to study the impact of operating conditions on the technical condition of hydraulic cylinders of a forklift truck. The objects of research were selected 18 forklifts with a load capacity of 5 tons, which are widely used in sea and river ports. The volume of overloaded cargo and operating conditions differed slightly during the year. The inspection of loaders was carried out once a year for 3 years, during the technical inspection period. Visual inspection (control) and inspection of hydraulic systems, brakes was carried out by the loader driver before and after the end of work. The analysis of the obtained data showed that the seal is the weakest link of hydraulic cylinders, during operation not only the SEALs wear out, but also the rods and sleeves, which leads to an increase in fluid leaks, a decrease in efficiency, and loss of performance.